Integrated Identity Tag System for Biodiversity Collections in Indonesian Botanical Garden Using QR Code - Apriyanto, Heri; Anggraeni, Citra Dewi (Program Studi Sistem Informasi Fakultas Teknik dan Ilmu Komputer, 2024)
In the year 2023, Indonesia has more than 40 botanical gardens. The garden has an essential role as the last defence in terms of plant conservation in Indonesia. However, some problems are commonly faced in the daily management process of plant collections, especially in the inspection of plant collection activity. There are no proper records of inspection activity, wrong identification of plant collection identity, inefficient reporting system, and the lack of visualisation documentation are part of the issues. Considering the essential inspection activity of plant collection in terms of conservation in the botanical garden, the use of a QR code that is integrated into the information system of plant collection management could be an alternative to be implemented to solve the issues. The implementation of the QR code can help to identify plant collection identity, history of collection and reporting process. Every plant collection will have an identity card with a QR code. Inspection officers can access the plant collection data by scanning the QR code using a smartphone. Thus, wrong identification could be minimised, reporting process could be more efficient, and inspection activity could be recorded as a history of plant collection. In addition, basic information about plant collection can also be accessed by visitors to educate them about biodiversity and conservation.